Sharing information across company borders in industry 4.0 - Kai-Ingo Voigt; Julian Müller; Johannes Veile; Marie-Christin Schmidt (Artificial Intelligence and Digital Transformation in Supply Chain Management: Innovative Approaches for Supply Chains. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 27, 2019)
Purpose: Industry 4.0's potentials can only unfold exhaustively if information is shared across company boarders and along supply chains. Exchanging information, however, implies several challenges for companies. This holds especially true if it is transmitted automatically and digitally, as promoted by the concept of Industry 4.0. In response to these challenges, this paper analyzes how information sharing changes in Industry 4.0 contexts. Methodology: Expert interviews with 17 representatives from supply chain management departments of German industrial enterprises provide the study's database. Hereby, the renowned SCOR-model serves as a theoretical foundation to classify the insights gained during the interviews. Findings: The types of information shared in supply chains, changes in the way information is shared, and initiatives to intensify information exchange in Industry 4.0 contexts are identified. These findings are analyzed against the background of the SCOR-dimensions plan, source, make, deliver and return. Originality: Information sharing, a vital basis for intended horizontal and vertical integration within the concept of Industry 4.0 has scarcely been investigated in extant literature.
urn:nbn:de:gbv:830-882.054113; 10419/209196; https://econpapers.repec.org/RePEc:zbw:hiclpr:27
Keywords: 650; Industry 4.0; Industrial internet of things; Supply chain management; Information sharing